Anesthetic management of a patient with multiple sclerosis - case report - Zuccolotto,Eduardo Barbin (2016)
Abstract Background and objectives: Multiple sclerosis is a demyelinating disease of the brain and spinal cord, characterized by muscle weakness, cognitive dysfunction, memory loss, and personality disorders. Factors that promote disease exacerbation are stress, physical trauma, infection, surgery, and hyperthermia. The objective is to describe the anesthetic management of a case referred to urological surgery. Case report: A female patient, 44 years of age, with multiple sclerosis, diagnosed with nephrolithiasis, referred for endoscopic ureterolythotripsy. Balanced general anesthesia was chosen, with midazolam, propofol and remifentanil target-controlled infusion; sevoflurane via laryngeal mask airway; and spontaneous ventilation. Because the patient had respiratory difficulty presenting with chest wall rigidity, it was decided to discontinue the infusion of remifentanil. There was no other complication or exacerbation of disease postoperatively. Conclusion: The use of neuromuscular blockers (depolarizing and non-depolarizing) is a problem in these patients. As there was no need for muscle relaxation in this case, muscle relaxants were omitted. We conclude that the combination of propofol and sevoflurane was satisfactory, not resulting in hemodynamic instability or disease exacerbation.